Об универсальном центральном сильном (слабом) взаимодействии тел и частиц. - Л. А. Агаловян (ՀՀ ԳԱԱ հրատ.)
Առաջարկված է մարմինների (մասնիկների) փոխազդեցության կենտրոնական ուժային (1.1) ունիվերսալ մոդել, համաձայն որի, կարճ հեռավորությունների դեպքում փոխազդեցության ուժը գերազանցում է նյուտոնյան տիեզերական ձգողության ուժին, իսկ, համեմատաբար մեծ հեռավորությունների վրա, գործնականում համընկնում է նրա հետ: It is theoretically shown the possibility of existence of such a universal among bodies, (particles,) central interaction which in small distances differs from Newton’s interaction and is stronger of it, and in considerably big distances practically coincides with Newton’s gravitational interaction. This interaction is given by formula (1.1).
Keywords: Mathematics; Science